The influence of slag and PSAC on the wear resistance of composite aluminium - Sulaiman, Zulkifli (2013)
This research involves the fabrication of aluminum composite by using Palm Shell Activated Carbon (PSAC) and Boiler Slag as reinforcements. The method used is powder metallurgy. For aluminum composite fabrication process, set compaction pressure of 200 MPa and sintering temperature was at 500°c and for 2 hours. Composite samples produced from pure aluminum as a matrix and PSAC and Boiler Slag as reinforcement. All samples were set at 80% pure aluminum while the ratio of reinforcements is as follows; sample A, 0% PSAC, 0% Boiler Slag; sample B, 0% PSAC, 20% Boiler Slag; sample C, 2% PSAC, 18% Boiler Slag; sample D, 4% PSAC, 16% Boiler Slag; sample E, 6% PSAC, 145 Boiler Slag; sample F, 8% PSAC, 12% boiler Slag and sample G,10% PSAC, 10% Boiler Slag. These composites were tested using wear test (ASTM G99-95, 2000). The composites were also tested for hardness, density, porosity and microscopic test. Based on the wear test, is found that PSAC and Boiler Slag enforcement influence the wear rate of the aluminum composite produced. For the best wear resistance, composite composition is 80% Al, 2% PSAC and 18% Boiler Slag. Based on the observation of the microstructure of aluminum composite produced, is found PSAC and Boiler Slag particles still in original condition. This indicates it is appropriate to provide aluminum composite reinforcements. Based on the porosity test, is found PSAC and Boiler Slag enforcement influence the rate of porosity aluminum composite produced. Density test shows the contents of PSAC and Boiler Slag enforcement influence the density of the composite. Hardness test showed the contents of PSAC and Boiler Slag enforcement influence the hardness of the composite. Aluminum composite containing 80% Al, 2 PSAC% and 18% Slag is the most hard. Aluminum composite produced potential as automotive and motorcycle components. Keyword; Aluminum Composite, Palm Shell Activated Carbon (PSAC), Boiler Slag, Wear Resistance.